“Factores asociados a la hipertensión en adultos, playas 2023” - Herrera Zamora, Jenny Estefania (2024)
Arterial hypertension is a chronic condition prevalent in older adults, characterized by persistently increased blood pressure and associated with other health problems. In the context of an aging global population, its prevalence generates significant concerns for both individual health and public health systems. The research focused on determining the factors that contributed to the prevalence of arterial hypertension in adults, and highlighted the importance of addressing this condition given its high incidence rate and significant implications for quality of life and cardiovascular health, based on a theoretical framework that framed the definition and risk factors of arterial hypertension, contextualizing these aspects within the aging and living conditions of older adults. The study was descriptive with a cross-sectional and retrospective elements, emphasizing risk factors in rural and urban areas, with a random sample reflecting socio-economic and cultural diversity. Identifying non-modifiable risk factors such as sex, age, family history and modifiable risk factors: consumption of inadequate food, alcohol, tobacco, sedentary lifestyle, and lack of medical check-ups. Fulfilling the general objective by determining the factors associated with arterial hypertension in adults residing in rural and urban areas of the Playas canton in the year 2023, for which a survey was applied to 100 patients who met the inclusion requirements. It was concluded that the most significant factors were: sedentary lifestyle with 97% of patients who do not engage in physical activity, inadequate diet since only 33% consume foods with fruits and vegetables and lack of medical checkups where 70% of them never go to medical checkups despite having knowledge of their pathology.